Immunization With a Pneumococcal Polysaccharide Vaccine in Children With Juvenile Idiopathic Arthritis Without Systemic Manifestations: a Prospective Study - Ekaterina I. Alexeeva; Tatiana M. Dvoryakovskaya; Rina V. Denisova; Ksenia B. Isaeva; Margarita A. Soloshenko; Anna V. Mamutova; Nikolay A. Mayansky; Natalia E. Tkachenko; Irina V. Zubkova; Tatiana A. Kaluzhnaya; Firuza Ch. Shakhtakhtinskaya; Anna G. Gayvoronskaya; et al. (Вопросы современной педиатрии)
Background. Patients with juvenile idiopathic arthritis (JIA) have an increased risk of being infected. Approximately half of all serious infections in children with JIA are associated with airway involvement.Objective. Our aim was to study the efficacy and safety of the pneumococcal 13-valent conjugate vaccine (PCV) in children with JIA.Methods. In a prospective cohort study, 5 groups were formed:  children with JIA in the remission phase on methotrexate therapy  (group 1) or etanercept (group 2), with JIA in the active phase prior  to the appointment of methotrexate (group 3) or etanercept (group  4), control group (conditionally healthy children). 0.5 ml of the 13-valent PCV was administered once subcutaneously during therapy in patients in the remission phase or 3 weeks before the appointment  of methotrexate or etanercept in patients in the active phase. The  main study outcome was the proportion of patients with a protective  ( 40 mg/L) level of specific anti-pneumococcal antibodies (anti-SPP) IgG to Streptococcus pneumoniae 4 weeks after vaccination. In  addition, we assessed the incidence of infectious events before and  after vaccination as well as changes in the content of a high-sensitivity C-reactive protein, S100 protein, and post-vaccination period.Results. The study included 125 children. Four weeks after  vaccination, the protective level of anti-SPP IgG was established in  21 (84%) patients in the 1st, 23 (92%) in the 2nd, 22 (88%) in the  3rd, 24 (96%) in the 4th and 5th groups (p =1.0). Increase in the  concentration of S100 protein and high-sensitivity C-reactive protein  after vaccination was not noted. JIA exacerbation episodes were not  recorded in any patient. After immunization, the total number of infectious events decreased in all observed groups (p 0.001). Serious adverse events were not registered during the study.Conclusion. Vaccination with the 13-valent PCV in children with JIA  is highly effective and is not accompanied by the development of serious adverse events.